2008
DOI: 10.1007/s11947-008-0053-2
|View full text |Cite
|
Sign up to set email alerts
|

Dextransucrase Stability in Cashew Apple Juice

Abstract: The use of agriculture waste as substrate for biotechnological process became an interesting alternative to reduce production costs and the negative impact of agricultural wastes disposal in the environment. In Brazil, cashew tree cultivation is done aiming the cashew nut production, and tons of cashew apples are wasted in the field after the nut removal. Thus, cashew apple juice can be used as low cost substrate for biotechnological process. In this study, the stability of dextransucrase produced in a ferment… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
24
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(29 citation statements)
references
References 36 publications
4
24
0
1
Order By: Relevance
“…Cashew apples are rich source of carbohydrates, minerals, vitamins, amino acids, carotenoids, phenolics, organic acids, and antioxidants and considered as source of energy (1)(2)(3). Besides possessing nutritional properties, these are not consumed like other fruits due to astringency.…”
Section: Introductionmentioning
confidence: 99%
“…Cashew apples are rich source of carbohydrates, minerals, vitamins, amino acids, carotenoids, phenolics, organic acids, and antioxidants and considered as source of energy (1)(2)(3). Besides possessing nutritional properties, these are not consumed like other fruits due to astringency.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, under static condition, cells grew well but, dextransucrase activity decreased adversely. Some other authors have reported 180 rpm, 150 rpm and 200 rpm (Dols et al, 1998;Honorato and Rodrigues, 2010;Sawale and Lele, 2010a) for the production of dextransucrase. Contrary to above given results, L. mesenteroides T3 gave best results (3.1 U/mL) at static condition in the recent report (Miljkovic et al, 2017).…”
Section: Optimization Of Agitation Ratementioning
confidence: 98%
“…The optimum fermentation time for L. mesenteroides FT 045, L. mesenteroides CMG713 and L. mesenteroides NRRL B-512 (F) were reported to be 8 h, 20 h and 6 h respectively (Cortezi et al, 2005;Sarwat et al, 2008;Honorato and Rodrigues, 2010). Whereas, 48 h and 8 h of incubation periods have been reported for maximum dextransucrase production by Lactobacillus acidophilus ST76480.01 and W. confusa (Rania et al, 2013;Zafar et al, 2018) Incubation time (h) …”
Section: Optimization Of Incubation Timementioning
confidence: 99%
See 1 more Smart Citation
“…Although cashew apples can be consumed as juice, ice-cream and other foodstuffs, the cashew tree cultivation in Brazil is an activity that aims mainly to produce cashew nuts. The nuts represent only 10% of the total fruit weight, and large amounts of cashew apples are left in the field after the removal of the nut [17].…”
Section: Introductionmentioning
confidence: 99%